Penanaman Nilai-nilai Islam Pada Anak - Siswadi Siswadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract:Parents, communities and governments put great attention to education of children, knowing that the quality of early childhood is a reflection of the quality of the nation in the future. So it can be said that the condition of children in Indonesia is now a picture of human resources in the future. In Islam, a child has a vertical relationship with God as creator, and horizontal relationships with parents and communities are responsible for educating him to be a religious man. Although the incidence of human nature state that a child (baby) is holy, but he has the potential to be good through the cultivation of religious values early and proper education. When a coaching is wrong, it causes people to be evil and bad. This could be due to either foster care, regardless of the value of education and religious norms. Key words: Investment Islamic values and age of the child.